Animated Video Strategy and Positive Reinforcement for Toilet Training Children Aged 1-3 Years in Saung Naga Village [Strategi Video Animasi dan Penguatan Positif untuk Toilet Training Anak 1–3 Tahun di Desa Saung Naga] - Suparno, Suparno; Estiani, Meilia (Indonesia Berdaya, 2025)
Abstract. In a previous community service activity conducted in the working area of Puskesmas Tanjung Agung, children aged 1–3 years were found to be unprepared for toilet training. A total of 33.4% of children were unable to verbally express their need to urinate or defecate, and were not yet able to communicate this need in the bathroom. Additionally, 86.7% of children were unable to remove their lower garments independently. Parents, especially mothers, had not received any education on positive reinforcement techniques and modeling through animated videos as a medium for toilet training. This activity aimed to increase maternal knowledge and provide hands-on experience in implementing toilet training strategies through modified positive reinforcement and modeling using animated videos. The evaluation results showed an 80.7% increase in maternal knowledge after the activity. Mothers also gained practical experience by using star charts as a form of positive reinforcement and animated videos as a modeling medium. This strategy proved effective, as evidenced by the success of participating children in achieving all seven indicators of successful toilet training. In conclusion, this community service activity successfully enhanced maternal knowledge and skills in applying modified positive reinforcement techniques and modeling using animated videos to train children aged 1–3 years in toilet training. Abstrak. Pada kegiatan pengabdian sebelumnya di wilayah kerja Puskesmas Tanjung Agung, ditemukan anak usia 1–3 tahun yang belum siap menjalani toilet training. Sebanyak 33,4% anak belum mampu mengungkapkan keinginan buang air kecil (BAK) atau buang air besar (BAB) secara verbal, dan belum dapat menyampaikannya di kamar mandi. Selain itu, 86,7% anak belum mampu membuka pakaian bawah secara mandiri. Belum pernah diberikan edukasi kepada orang tua, khususnya ibu, mengenai teknik penguatan positif dan modeling melalui video animasi sebagai media toilet training. Kegiatan ini bertujuan untuk meningkatkan pengetahuan dan memberikan pengalaman langsung kepada ibu mengenai strategi toilet training melalui modifikasi penguatan positif dan modeling berbasis video animasi. Hasil evaluasi menunjukkan peningkatan pengetahuan ibu sebesar 80,7% setelah kegiatan. Para ibu juga mendapatkan pengalaman langsung melalui penerapan bagan bintang sebagai bentuk penguatan positif dan penggunaan video animasi sebagai media modeling. Strategi ini terbukti efektif, ditunjukkan oleh keberhasilan anak peserta dalam memenuhi tujuh indikator keberhasilan toilet training. Kesimpulannya, kegiatan pengabdian ini berhasil meningkatkan pengetahuan dan keterampilan ibu dalam menerapkan teknik penguatan positif dan modeling menggunakan video animasi untuk melatih toilet training pada anak usia 1–3 tahun.